Predictors of Success following Microvascular Replantation Surgery of the Upper Extremity in Adult Patients. Issue 9 (14th September 2022) - Rizzo, Kayla R.; Eckhoff, Michael D.; Gonzalez, Gilberto A.; Diamond, Shawn; Nesti, Leon; Dunn, John C.
Abstract : Background: The purpose of this study is to ascertain which factors are associated with successful replantation in the upper extremity. Secondarily, the purpose was to determine patient factors that differentiate those patients who undergo initial replantation versus initial amputation. Methods: Data gathered for this retrospective study were obtained from a custom subset of the 2015–2020 IBM Truven MarketScan Commercial and IBM Truven MarketScan Medicare Supplemental databases. Data were sorted using Current Procedural Terminology codes and International Classification of Disease, Ninth and Tenth Revision, diagnosis codes. Results: Increasing age was significantly associated with undergoing initial amputation compared with replantation ( P < 0.001; 95% CI, 47.146–50.654). Among comorbid conditions, patients with diabetes mellitus type II (2.4% versus 24.3%; P < 0.001), hypertension (11.9% versus 28.0%; P = 0.03), end-stage renal disease (0% versus 10.5%; P = 0.03), and hypertensive chronic kidney disease (0% versus 8.7%; P = 0.04) more commonly underwent an initial amputation procedure. When evaluating the need for secondary procedure after replantation, there was no statistical significance between groups when comparing age, gender, insurance type, general comorbidities, connective tissue disorders, mental health disorders, or geographic location. Conclusions: In conclusion, this study demonstrates that age and the presence of comorbidities are important factors in the differentiation of which patients undergo initial reimplantation versus initial amputation. Additionally, no specific factors were identified that were associated with secondary procedures after replantation.